The Prophet’s Morality and Its Application in Daily Life: A Comparative Perspective of Ustadz Abdul Somad and Ustadz Adi Hidayat - Alihan Satra; Migo Ahmad Syumus Shalahuddin; Putri Melati; Muhammad Azhari (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This article discusses the importance of emulating the character of Prophet Muhammad (peace be upon him) and applying it in daily life, based on the perspectives of two prominent Islamic scholars, Ustadz Abdul Somad and Ustadz Adi Hidayat. The Prophet is well known for his noble character, which encompasses various aspects of life ranging from his relationship with God and fellow human beings to the natural environment. According to Ustadz Abdul Somad, the Messenger of Allah is not only a moral exemplar but also a guide for navigating modern life. Ustadz Adi Hidayat, on the other hand, emphasizes that emulating the Prophet's character is a profound expression of faith in Islamic teachings. This article outlines various examples of the Prophet’s moral conduct such as honesty, patience, humility, and compassion and how these principles can be applied in the daily lives of Muslims to help build a better society. Drawing from the lectures of both scholars, the article aims to provide insights into the contemporary relevance of the Prophet’s character and encourages Muslims to use it as a model in their interactions with others, whether in family, professional, or social settings.